Formation of 2, 3-dihydro-3, 5-Dihydroxy-6-Methyl-4(H)-Pyran-4-One (DDMP) in glucose-amino acids Maillard reaction by dry-heating in comparison to wet-heating. (May 2019) - Li, He; Tang, Xiang-Yi; Wu, Chun-Jian; Yu, Shu-Juan
Abstract: The 2, 3-dihydro-3, 5-dihydroxy-6-methyl-4(H)-pyran-4-one (DDMP) is one of the Mallard reaction product with intense bitter and strong antioxidant activity. Insight into DDMP formation pathways is important to manage Maillard reaction products quality. In this work, wet- and dry-heating glucose-amino acid model reactions were investigated to understand the DDMP formation pathways. Lysine and proline facilitated the DDMP generation in wet- and dry-heating system, respectively, suggesting the reaction intensity and amino acid properties are primary factors mediating DDMP generation. Fundamental mechanism on DDMP formation or inhibition was evaluated via quantitatively monitoring enolization products, which suggested that the formation of DDMP was facilitated at lower moisture content condition caused by more 1-deoxyglucosone (1-DG) generation via 2, 3-enolization. However, increasing moisture content resulted in the decay of DDMP because of the transformation of 2, 3-enolization to 1, 2-enolization, which inhibited DDMP generation but transformed to form 5-hydroxymethylfurfural (HMF). Highlights: Maillard reaction intensity is a leading role in DDMP generation in aqueous systems. Amino acid property is a primary factor in DDMP formation in dry systems. Lower moisture facilitated the 2, 3-enolization to form DDMP in Glc-Pro system. Higher moisture content facilitated the 1, 2-enolization to form HMF.